2020
DOI: 10.1016/j.cub.2020.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish Retinal Ganglion Cells Asymmetrically Encode Spectral and Temporal Information across Visual Space

Abstract: Summary In vertebrate vision, the tetrachromatic larval zebrafish permits non-invasive monitoring and manipulating of neural activity across the nervous system in vivo during ongoing behavior. However, despite a perhaps unparalleled understanding of links between zebrafish brain circuits and visual behaviors, comparatively little is known about what their eyes send to the brain via retinal ganglion cells (RGCs). Major gaps in knowledge include any information on spectral codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 86 publications
(200 reference statements)
8
105
0
Order By: Relevance
“…Also, the responses in the RAs were more color specific than the responses in RGCs, with a tendency for one or two color stimuli to dominate the response.To better probe the variability of the responses, we constructed a linear model to infer the required cone type's gains (amount of response contribution) yielding a given ROI response [15,17] . As has been reported before, gains of the UV cones were considerably higher than those of the other cone types, and blue gains were mostly negative, indicating they have Off polarity [8,(18)(19)(20) ). The distribution of the gains of RGCs and RAs were very similar, so we identified the patterns present in the combinations of gains to probe for potential differences.…”
supporting
confidence: 79%
See 4 more Smart Citations
“…Also, the responses in the RAs were more color specific than the responses in RGCs, with a tendency for one or two color stimuli to dominate the response.To better probe the variability of the responses, we constructed a linear model to infer the required cone type's gains (amount of response contribution) yielding a given ROI response [15,17] . As has been reported before, gains of the UV cones were considerably higher than those of the other cone types, and blue gains were mostly negative, indicating they have Off polarity [8,(18)(19)(20) ). The distribution of the gains of RGCs and RAs were very similar, so we identified the patterns present in the combinations of gains to probe for potential differences.…”
supporting
confidence: 79%
“…Additionally, their entire eye and nervous system are accessible to imaging, given they are naturally transparent [3][4][5] . Relying on this advantage, recent research has found that, through a set of color specific horizontal, bipolar and retinal ganglion cells (RGCs) [6][7][8] , the eye then relays tetrachromatic information to several retino-recipient areas (RAs) [9,10] . The main RA is the optic tectum, receiving 97% of the RGC axons via the neuropil mass termed Arborization Field 10 (AF10) [11,12] .…”
mentioning
confidence: 99%
See 3 more Smart Citations